Group II intron lariat: Structural insights into the spliceosome - Peters, Jessica K (RNA Biol, 2015)
Group II introns are self-splicing catalytic RNAs found in bacteria and the organelles of fungi and plants. They are thought to share a common ancestor with the spliceosome, which catalyzes the removal of nuclear introns from pre-mRNAs in eukaryotes. Recent structural and biochemical evidence supports the hypothesis that the spliceosome has a catalytic RNA core homologous to that found in group II introns. The crystal structure of a eukaryotic group IIB intron was recently determined and reveals the architecture of a branched lariat RNA that is also formed by the spliceosome. Here we describe the active site components of this intron and propose a model for RNA splicing involving dynamic base triples in the catalytic triad. Based on this structure, we draw analogies to the U2/U6 snRNA pairing and RNA-protein interactions that form in the active site of the spliceosome.